" Alienation, Ferocity, and Rhetoric of Confusion in Harold Pinter’s The Birthday Party - Othman.O.Ahmed, Kawa (International Journal of Language and Literary Studies, 2024)
Printer’s ‘The Birthday Party’ has received considerable recognition among literary critics over the last decade. This is mostly due to the fact that Pinter abandons the traditional portrayal of characters. Many critics, however, scarcely paid attention to the significance of the characters’ linguistic style, particularly, the extent the players’ rhetoric is used as a means for confusion and manipulation. As this research explains, Printer’s play exposes the ferocious and confusing functions of language beyond its normal function as a means of productive communication. To do so, the research concisely analyses the rhetorical style of the two main antagonists in The Birthday Party as they try to control and manipulate the main protagonist linguistically. The play also, as the research explains, reveals the link between the lack of communication among characters in a domestic space and the development of a sense of loss and alienation by the main protagonist.